Biomineralization of Calcium Phosphate Crystals Controlled by Protein-Protein Interactions - Duman, Elif; Kehribar, Ebru Sahin; Ahan, Recep Erdem; Yuca, Esra; Seker, Urartu Ozgur Safak (AMER CHEMICAL SOC, 2019)
Hydroxyapatite (HAP) is the major biomineral of bone. Despite the large number of studies addressing HAP formation, a fundamental understanding of the critical roles of HAP-forming proteins in vitro is needed. Effects of two HAP-interacting proteins, osteocalcin (OCN) and osteopontin (OPN), on HAP formation was investigated via in vitro biomineralization experiments, and their outcomes on the crystal structure of calcium phosphate (CaP) was revealed. Our data suggest that OCN concentration is negatively correlated with crystal formation rate and crystal size, yet the presence of OCN leads to a more ordered HAP crystal formation. On the other hand, OPN protein promotes faster formation of CaP crystals potentially working as a growth site for mineral formation, and it decreases the Ca:P ratio. This effect results in a shift from HAP-type minerals to less ordered crystals. The crystal size, shape, and Ca:P ratio can be tuned to design improved mammalian hard tissue environment-mimicking matrices by taking advantage of the OCN and OPN proteins on crystal formation. We believe our current findings will lead to innovative approaches for bone biomineralization in regenerative medicine.
Keywords: biomineralization; hydroxyapatite crystals; protein-protein interaction; DENTIN MATRIX PROTEIN-1; ALKALINE-PHOSPHATASE; IN-VITRO; ESCHERICHIA-COLI; BONE-FORMATION; HYDROXYAPATITE FORMATION; OSTEOPONTIN; OSTEOCALCIN; BINDING; NUCLEATION; Materials Science